Public Housing in Israel: From Welfare State to Neoliberalism - Ravit Hananel (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper analyzes and explains the evolution of public housing in Israel. Compared to other countries, Israel’s public housing has undergone massive change throughout the last few decades, and is therefore an interesting case study. In the 1950s and 1960s, public housing made up 60% of the state’s total housing stock, and most of the population was eligible. Today, however, public housing is marginal in scope and earmarked for only 1.9% of the population, most of which come from the poorest households. This study presents the explanation of these changes and the current state of public housing in Israel.